The Impact of Third-Party Funds, Capital Adequacy, and Operational Costs on Financing Distribution - Awang Ulianti; Gustika Nurmalia (Department of Islamic Banking, 2025)
Purpose – This study aims to determine the impact of third-party funds, Capital Adequacy Ratio, and operating expenses on operating income (BOPO) in the distribution of financing at PT. BPRS Mitra Agro Usaha Bandar Lampung during the period 2014-2024. Methodology – The approach used in this study is quantitative, employing a multiple linear regression analysis method with the EViews 10 program. The data analyzed are secondary data derived from the bank's annual financial statements in the last eleven years. Findings – The results showed that the variable deposits have a positive and significant impact on the distribution of financing. On the other hand, CAR showed a negative and significant impact on the distribution of financing. Meanwhile, BOPO has a positive and significant influence on the distribution of financing. Simultaneously, DPK, CAR, and BOPO have a significant influence on the distribution of financing at PT. BPRS Mitra Agro Usaha Bandar Lampung. Implications – The results of this study are expected to serve as the basis for management considerations at PT. BPRS Mitra Agro Usaha Bandar Lampung is optimizing the collection of deposits and operational efficiency to improve the distribution of financing. In addition, these findings can also serve as a reference for regulators in formulating policies that support the stability and sustainable growth of Shariah rural banks. Originality – This study demonstrates originality in assessing the simultaneous influence of DPK, CAR, and BOPO on the distribution of financing at BPRS, a topic that is still rarely explored specifically in the context of PT. BPRS Mitra Agro Usaha Bandar Lampung.